2019
DOI: 10.3389/fvets.2019.00221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peste des Petits Ruminants Transmission Hotspots in the Karamoja Subregion of Uganda for Targeting of Eradication Interventions

Abstract: This paper describes an assessment of the patterns of peste des petits ruminants virus circulation in the Karamoja subregion of Uganda conducted to identify the communities that maintain the virus and inform the development of a targeted vaccination strategy. Participatory epidemiological methods were used to develop an operational hypothesis for the patterns of PPR in Karamoja that was subsequently validated through outbreak investigation and genomics. The participatory epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…The reported strains from the DRC in 2017 also cluster with strains detected later in 2018 from different locations in North Kivu, suggesting a local PPRV circulation in this sedentary agro-pastoral system [49]. These findings align with recent observations in the Karamoja region in northeastern Uganda; despite being large pastoral systems, separate foci for transmission and PPRV maintenance were identified within relatively small but probably transboundary areas [23]. Our results also support the importance of regionally coordinated actions and locally adapted strategies to stablish effective PPR surveillance and control.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The reported strains from the DRC in 2017 also cluster with strains detected later in 2018 from different locations in North Kivu, suggesting a local PPRV circulation in this sedentary agro-pastoral system [49]. These findings align with recent observations in the Karamoja region in northeastern Uganda; despite being large pastoral systems, separate foci for transmission and PPRV maintenance were identified within relatively small but probably transboundary areas [23]. Our results also support the importance of regionally coordinated actions and locally adapted strategies to stablish effective PPR surveillance and control.…”
Section: Discussionsupporting
confidence: 84%
“…PPRV lineage II, III, and IV have circulated in different countries and regions from East Africa [14,23,42,51]. This study, together with recent works [49,50], reports the circulation of PPRV lineage III in the northern Albertine Rift area causing the first-known PPR outbreaks in this region from 2016 onwards.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, based on partial genome sequencing, the virus strains detected in this study were almost identical, and therefore the variation in observed clinical signs between the four flocks from which sequences were obtained ( Table 1) was most likely due to host or environmental factors or co-infections rather than virus genotype. The circulation of multiple lineages of PPRV in Tanzania reflects multiple introductions, most likely through transboundary movements of infected small ruminants for trade or migration from neighbouring countries where PPRV is also considered to be endemic and multiple lineages have been detected-Kenya, Uganda, Rwanda, Burundi and the Democratic Republic of the Congo [66][67][68][69][70]. However, the live attenuated PPRV vaccine (Nigeria/75/1) is reported to provide protection against all the lineages [71].…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, a participatory epidemiological assessment included risk mapping with livestock owners, community animal health workers and veterinarians. This indicated that there were two critical foci of virus transmission on the Uganda-Kenya border [24]. Better communication is also essential for developing and influencing people's attitudes, behaviour and decisions concerning the control of PPR.…”
Section: Applying Movement Controls and Providing Better Channels Formentioning
confidence: 99%